Effects of continuous biochar application on soil chemical properties and tomato yield and quality in an arched shed - Sun, Chitao; Niu, Rongxing; Cao, Gang; Feng, Di (Frontiers in Plant Science, 2025)
Biochar is a promising soil amendment, but its long-term consecutive effects on greenhouse tomato systems are insufficiently explored. To investigate the dynamic and accumulative effects of consecutive biochar application on soil chemical properties and tomato (Solanum lycopersicum L.) yield and quality, a three-year arched shed field experiment was conducted with five biochar rates: 0 (CK), 0.5 (T1), 1.0 (T2), 2.0 (T3), and 4.0 (T4) kg·m-². Soil chemical properties, tomato growth, yield components, and fruit quality were analyzed. Results showed biochar slightly increased soil electrical conductivity (all below salinization threshold); only T4 significantly raised soil pH (by 0.4 units) and organic matter (by 132.8%) vs. CK. Annual differences in soil available potassium diminished to non-significance, while available phosphorus was 50.8% (T2) and 63.0% (T3) higher than CK. Tomato plant height and dry matter increased with biochar rate; T1-T4 improved fruits per plant (2.0%-17.0%) and single fruit weight (7.0%-16.0%) over CK, with T2 (13.7%-24.1%) and T3 (19.8%-33.2%) achieving the highest significant yield increases. For quality, T2 had the highest comprehensive index, followed by T1 and T3, with their three-year average scores up by 33.1%, 15.4%, and 15.4% respectively. In conclusion, 1.0-2.0 kg·m-² biochar optimally enhanced tomato yield and nutritional/organoleptic quality, with no significant interannual cumulative effects of biochar rate on yield or quality—providing theoretical and technical support for high-quality greenhouse tomato production.